Sustentabilidade e qualidade do solo em propriedades de cana-de-açúcar orgânica e convencional - Oliveira, Fernanda Ribeiro de Andrade (2008)
Soil quality evaluation is an important strategy, as it allows producers to focus agriculture techniques to constantly develop and maintain adequate, selfsustainable productions equilibrium. This study evaluated rural activities environmental impact by the system APOIA-NovoRural, as well as the influence of different sugarcane production systems on soil quality through physical, chemical and biochemical indicators. Six sugarcane aguardente production establishments were selected in Piracicaba, Socorro, Jaguariúna, Holambra e Ribeirão Preto, in the state of São Paulo, Brazil. In each property two treatments were studied, sugarcane cultivated soil under organic or conventional system and, soil under native forest, taken as basal reference. The APOIA-NovoRural indicated better environmental performance on the organic than conventional system, emphasizing the establishments landscape ecology and administration. Most indicators pointed out better soil conservation contribution by organic system. Among them, aggregate stability (Ea), organic matter (MO), dehydrogenase (Des), polysaccharides (Poli) and microbial biomass (Bm) can be used as system sustainable indicators. Isolated values don t work as reliable and accurate indicators for soil conditions, however, when evaluated together through Principal Components Analysis (PCA), they are able to show the alterations occurring in the environment due to the different handling of the soil. Thus, the selected attributes can provide subsidy to a correct land use.